Surgical Management of Parapharyngeal Metastases from Thyroid Carcinoma: A Systematic Review and Patient-Level Analysis of the Role of Lateral Neck Dissection - Francesco Chiari; Marika Reppucci; Matteo Fermi; Giulia Di Dalmazi; Vincenzo Palatino; Daria Maria Filippini; Giovanni Motta; Giuseppe Mercante; Livio Presutti; Claudio Donadio Caporale; Pierre Guarino (Cancers, 2026)
Background/Objectives: Parapharyngeal space (PPS) metastases from thyroid carcinoma are rare, and evidence guiding their surgical management, particularly the role of concomitant lateral neck dissection (LND) in patients with a clinically node-negative (cN0) neck, remains limited. This systematic review and patient-level analysis evaluated the clinicopathological characteristics, surgical management, and oncologic outcomes of PPS metastases, with particular emphasis on the management of the cN0 neck. Methods: A PRISMA 2020-compliant systematic review of PubMed, Scopus, and the Cochrane Library was performed. Patient-level data were analyzed according to clinical neck status and timing of PPS metastasis presentation. Results: Thirty-two studies including 162 patients were analyzed. Papillary thyroid carcinoma accounted for 94.4% of cases, while PPS metastases presented as primary disease in 48.8% and recurrent disease in 51.2% of patients. The transcervical approach (TCA) was the predominant surgical technique (79.1%), whereas LND was performed in 70.2% of patients with available data. Among the 19 patients with a cN0 neck, 10 had a previously undissected lateral neck; of these, 6 underwent elective LND and 4 underwent isolated PPS metastasectomy. No occult cervical lymph node metastases were identified following elective LND. Patients with recurrent PPS metastases had significantly higher overall recurrence (47.5% vs. 13.2%, p < 0.001) and disease-specific mortality (22.8% vs. 5.6%, p = 0.003) than those with primary PPS metastases. Conclusions: TCA remains the reference surgical strategy for PPS metastases from thyroid carcinoma. Although based on a very limited cN0 subgroup, current evidence suggests that routine elective LND may not be necessary in carefully selected patients presenting with isolated PPS metastases and a cN0 neck. Recurrent PPS metastases are associated with poorer oncologic outcomes.